Explaining exchange rate dynamics: the uncovered equity return parity condition - Lorenzo Cappiello; Roberto A. De Santis (European Central Bank (ECB), 2005)
By employing Lucas' (1982) model, this study proposes an arbitrage relationship – the Uncovered Equity Return Parity (URP) condition – to explain the dynamics of exchange rates. When expected equity returns in a country/region are lower than expected equity returns in another country/region, the currency associated with the market offering lower returns is expected to appreciate. First, we test the URP assuming that investors are risk neutral and next we relax this hypothesis. The resulting risk premia are proxied by economic variables, which are related to the business cycle. We employ differentials in corporate earnings' growth rates, short-term interest rate changes, annual inflation rates, and net equity flows. The URP explains a large fraction of the variability of some European currencies vis-à-vis the US dollar. When confronted with the naïve random walk model, the URP for the EUR/USD performs better in terms of forecasts for a set of alternative statistics.
Keywords: D82; G14; G15; 330; asset pricing; foreign exchange markets; GMM; random walk; UIP; Wechselkurs; Arbitrage Pricing; Zinsparität; Geldpolitik; EU-Staaten; USA